2000
DOI: 10.1103/physrevb.61.9867
|View full text |Cite
|
Sign up to set email alerts
|

Variation of theLDA+Umethod appropriate tof-state localization: Application to magneto-optical properties

Abstract: A variation of the local density approximation (LDA)ϩU method, appropriate for application to cerium f-state localization, and its implementation within a full-potential linear muffin-tin orbital method is described. The method, functionally similar to the self-interaction-corrected-pseudopotential method, is applied to a calculation of the optical conductivity and ground-state magnetic moments of the compounds CeSb and CeTe. We also briefly discuss application of the method to the equilibrium volume of fcc pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
22
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
3
22
0
Order By: Relevance
“…14 Several research groups 15,16,17 have applied the LDA+U method to include more f -f correlation energy. By adjusting the on-site Coulomb repulsion energy (U ) appropriately, it has been possible to fit to the experimental δ-phase volume.…”
Section: Introductionmentioning
confidence: 99%
“…14 Several research groups 15,16,17 have applied the LDA+U method to include more f -f correlation energy. By adjusting the on-site Coulomb repulsion energy (U ) appropriately, it has been possible to fit to the experimental δ-phase volume.…”
Section: Introductionmentioning
confidence: 99%
“…LDAϩU calculations for the heavier systems CeSb and CeTe increase the magnetic moment to 2.2 B and 1.4 B , respectively. 22 Similarly, we find that the LDAϩU method increases the magnetic moment for the lighter, more delocalized systems, CeP and CeS to 2.0 B and 1.9 B , respectively. Thus, the LDAϩU method enhances the magnetic moment across the entire series and fails to predict the trend of magnetic properties.…”
mentioning
confidence: 85%
“…Finally, we predict the experimentally observed change of the ground-state magnetic structure from the ͗001͘ AF-IA ͑↑↑↓↓͒ in CeBi and CeSb to the ͗001͘ AF-I ͑↑↓͒ in CeAs and CeP. In sharp contrast, the second, ab initio method, based on density functional theory within the local density approximation ͑LDA͒, 20,21 and on the LDAϩU scheme 22 fail to predict, even qualitatively, the trend of magnetism in this series of strongly correlated electron systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These unusual physical and mechanical properties 3 are believed to be caused by the itinerant-tolocalized crossover of 5f electronic orbitals 4 . Band-structure calculations within the local density approximation (LDA) fail to predict the equilibrium volume of the nonmagnetic δ-phase of Pu 8,9 ; while the LDA+U calculations gives the experimental δ-phase volume with an appropriate value of U but also indicates an instability toward an antiferromagnetic ground state [10][11][12] . Later LDA+U calculations [13][14][15][16] that included spinorbit coupling (SOC) suggested that the magnetism could be naturally quenched and that the correct δ-phase volume could be obtained if the Pu atom is in a closed-shell Pu 5f 6 configuration,.…”
Section: Introductionmentioning
confidence: 99%